Design of rice planting machine using ration of wheels rotation system - Mahirul Mursid; Ananda Trisukmo Utomo; Ahmad Khuluqul Amin; Liza Rusdiyana; Dedy Zulhidayat Noor; Nurhusodo (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2025)
The Rice planting process by “Kelompok Tani” in the Tulungagung, East Java is done manually, Manual planting requires a lot of manpower and very costly because the Landowner need to pay to the laborers to plant their Rice Paddy yet requires a lot of time to do the work until done completely and drains a lot of works and efforts. From that, the Rice planter is designed to reduce the planting process. The design concept adopted the “Jajar Legowo” Rice Planting method, with the distance arrangement applied from the Gears comparison so as to produce equal and uniform distances. This manpowered machine is expected to help The Farmers to shorten the planting process without incurring additional costs for Fuel. From the results of the planning and calculation produced a machine with capability of planting rice 26.4m2/ hour using number 40 of chain, sprocket size 242.80mm and Ratio of each sprockets are 1: 4 to produce a uniform planting. Using a 400mm long shaft for the planter and 10mm diameter with ST37 material. On wheels use Bearing with 30mm Bore.